Stuff you should know An incomplete compendium of mostly interesting things - Josh Clark; Bryant, Chuck; Parker, Nils. (London Trapeze, 2020)
Josh Clark and Chuck Bryant started the podcast Stuff You Should Know back in 2008 because they were curious-curious about the world around them, curious about what they might have missed in their formal educations, and curious to dig deeper on stuff they thought they understood. As it turns out, they aren't the only curious ones. They've since amassed a rabid fan base, making Stuff You Should Know one of the most popular podcasts in the world. Armed with their inquisitive natures and a passion for haring, they research and discuss a wide variety of topics-always working to uncover the weird, fascinating, delightful, or unexpected pieces of any given subject, and then talking about it together in an accessible and humorous way.The pair have now taken their near-boundless "whys" and "hows" from your earbuds to the pages of a book for the first time-and with it comes loads of new content, covering subjects about which they've long wondered or wanted to explore in greater detail. Follow along as they dig into the underlying stories and interesting ways things fit into the world, touching on everything from the origin of Murphy beds, to the history of facial hair, to the psychology of being lost. in additional layer of visual material allows the duo to further embellish their engaging storytelling and bring these topics to life in a snappy new way-including charts and graphs, illustrations, and sidebars for rabbit-hole tangents and wandering digressions.Have you ever wondered about the world around you, and wished to see the magic in everyday things? Come get curious with Stuff You Should Know. With Josh and Chuck as your guide, there's something interesting about everything.
Keywords: General